Substantiation of application and estimation of efficacy of probiotics at inflammatory bowel diseases - Ye. A. Poluektova; Yu. O. Sidorina; S. Yu. Kuchumova; A. V. Korolev; O. S. Shifrin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To prove competency of application of probiotics and to analyze data of the original studies of efficacy of various probiotic agents in treatment of inflammatory bowel diseases (IBD).Summary. The role of microflora in pathogenesis of this group of diseases becomes more and more obvious. At patients with IBD the intestinal microbiome have quantitative and qualitative differences from microbiome of healthy patients aside of increase in contents of opportunistic and pathogenic microorganisms. Microbiome changes result in initiation of cascade of pathological immune reactions of the host in related to presence of genetical defects, that, in turn, promotes development of clinical symptoms and morphological changes in intestinal wall. Potential of probiotic agents effect on microflora is actively studied in the last years, including patients with IBD.Conclusion. The highest efficacy the Bifidum and Lactobacilli-containing probiotics, possess at advance and maintenance of remission of reservoir ileitis (pouchitis). Addition of probiotics in mode of treatment significantly increases probability of clinical improvement and, at level of the statistical trend, achievement of clinical remission at ulcerative colitis. In remission maintenance efficacy of the studied probiotic drugs is comparable to efficacy of maintenance dozes of mesalazine. Efficacy of probiotics is not proved at their addition in the mode of standard therapy used for achievement and maintenance of remission of a Crohn's disease.